Respostas

2013-09-12T19:27:24-03:00
f(x)=x²-3x+2
Δ=b²-4.a.c= -3²-4.1.2
Δ=1
x= -b±√¯ /2a =
x= -(-3)
±√1¯/2.1
x=9±1/2

x’=9+1/2  
x’=10/2 =5
x”=9-1/2  
x”=8/2 = 4
-------------------
f(x)=x²-4x-5
x²-4x-5=0
Δ=b²-4.a.c = -4²-4.1.(-5)
Δ=36
x= -b±√¯ /2a =
x= -(-4)
±√36¯/2.1=
x=4±6/2
x’=4+6/2   
x’=10/2  
x’= 5
x”=4-6/2  
x”= -2/2  
x”= -1
-------------

f(x)=2x+18                      
  2x+18=0
   2x=0-18
   2x= -18
   x= -18/2
        x=-
9               













2 4 2
-18/2 = -9 desculpa por esse erro
no ultimo calculo